IMPLEMENTASI PERKARA PRODEO BAGI MASYARAKAT MISKIN DI PENGADILAN AGAMA KELAS 1A PADANG - Nofri Hartos; Asasriwarni . (UIN Imam Bonjol Padang, 2020)
This research is about the Implementation of Prodeo Cases for the Poor in the Class IA Religious Court of Padang. Problem in this research is why not all poor people who submit cases to the Padang Religious Courts get services through prodeo, and why those who do not fulfill the requirements can be granted prodeo, and how the implementation of the prodeo case in the Padang Religious Court. The objectives to be achieved in this research are: (1) to explain why not all poor people who filed cases to the Padang Religious Court received services by prodeo, (2) to explain why parties who did not meet the requirements turned out to be granted a prodeo, and (3) to explain how the implementation of prodeo cases in the 1A class of Religious Courts in Padang. This research is in the form of field research while the primary data sources are interviews at the Class IA Religious Courts of Padang, then secondary data in the form of laws, books and documents - the data collection techniques used are through literature studies and related documentation later. followed by interviews with Deputy Chairpersons, Registrars, Treasurers, Substitute Registrars and Posbakum, while data analysis used a descriptive method. The results of this research reveal that: The causes so that not all poor people who filed cases at the Padang Religious Court to obtain services in a prodeo were due to the lack of funds provided by the government to the Padang Religious Court which amounted to Rp. 31,500,000. for 105 cases in 2018 and Rp. 7,500,000. For 25 cases in 2017 and Rp. 4,800,000, for 16 cases in 2016, so as to even justice for the poor in the city of Padang, the Religious Court provides additional conditions in litigation, namely: (a) Application with the defendant must be in one area, namely the City of Padang, (b) Prodeo cases are only permitted in marriage cases, such as marriage, divorce, divorce divorce, and marriage dispensation, and (c) Prodeo cases can only be received in 3 (three) cases per week. Explanation of parties that did not fulfill the requirements turned out to be granted by prodeo because of the excess funds issued in the previous prodeo case. So that the funds do not return to the state, the Padang Religious Court grants the Defendant's case domiciled outside the city of Padang, but this is very risky, because there is no certainty about the funds to be spent on the case. If the funds can be sufficient, as long as it will be safe in case of case costs. The implementation of the prodeo case at the Padang Religious Court has been carried out as stipulated by Perma Number 1 of 2014. However, there are very few funds provided by the government for prodeo cases so that there are still many poor people in Padang City who have not been allocated prodeo in Class IA Religious Court Padang